Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Religiusitas Terhadap Loyalitas Kerja Amil Pada Organisasi Pengelola Zakat Kota Makassar - Nita, Nur; Wardy Putra, Trisno; Sofyan, Sofyan (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
The objective of this study is to ascertain the impact of the work environment, motivation, and religion on Amil's loyalty towards employment in zakat management organisations in Makassar City. This study employs a quantitative methodology. The population for this study consists of the amil/employees/staff members of OPZ Makassar City, namely BMM, Dompet Duafah, and Baznas Makassar City. The sampling approach employs a saturated sampling method that encompasses non-probability sampling. The data analysis approach used is the Classic Assumption Test and Hypothesis Test using the SPSS 23 software. The research results show that: 1) The work environment has a positive and significant effect on amil's work loyalty in zakat management organizations in Makassar City. 2) motivation does not have a positive and significant effect on Amil's work loyalty in the zakat management organization in Makassar City. 3) religiosity has a positive and significant effect on Amil's work loyalty in the Makassar City zakat management organization. 4) work environment, work motivation, and religiosity together have a positive and simultaneous influence on amil's work loyalty in zakat management organizations